PENGARUH PENDIDIKAN KESEHATAN MANFAAT HEMODIALISA TERHADAP MOTIVASI HARAPAN HIDUP PADA PASIEN GAGAL GINJAL KRONIK DI RUMAH SAKIT UMUM DAERAH H. SAHUDIN KOTA CANE TAHUN 2021 - Kristina; Kamaliah Ainun; Srimis Leini Saragih (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2021)
Hemodialysis is a process carried out to remove fluids and waste products from the body when the kidneys are no longer able to carry out the process. The purpose of the study was to analyze